Near‐Infrared Fluorescence/Photoacoustic Agent with an Intensifying Optical Performance for Imaging‐Guided Effective Photothermal Therapy. Issue 12 (30th September 2020) - Ye, Fengying; Huang, Weijing; Li, Chonglu; Li, Guangjin; Yang, Wen‐Chao; Liu, Sheng Hua; Yin, Jun; Sun, Yao; Yang, Guang‐Fu
Abstract: Near‐infrared fluorescent agents generally exhibit typical push‐pull electron characteristics, and their optical behaviors are closely related to their molecular structures. Benzobisthiadiazole moiety as a classic electron acceptor has been typically used to design the Donor‐Acceptor‐Donor (D‐A‐D) type of fluorescent/photoacoustic agents with emission in the second near‐infrared window. In this work, two strategies are examined to intensify their absorption/fluorescence and fluorescence/photoacoustic imaging performance: 1) the conjugated bridges are amplified by installing two electron‐rich thiophenes and one styrene on two sides of the benzobisthiadiazole core and 2) the N, N ‐dimethylamino group is employed to replace the traditional diphenylamine to strengthen the electron donor. This agent shows the maximum absorption and fluorescence emission at 942 and 1302 nm, respectively. Its superior in vitro and vivo data confirms that the nanoparticles of this compound complexed with 1, 2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐N‐[methoxy(polyethyleneglycol)] (DSPE‐PEG) can not only perform real‐time and high‐contrast noninvasive near‐infrared fluorescence/photoacoustic imaging of tumors (980 nm laser irradiation) but also effectively ablate the tumor cells by photothermal therapy implementing the dual‐modality imaging method. In particular, its longer wavelength absorption and emission successfully improves the fluorescence/photoacoustic imaging performance. These observations highlight its potential to be used as a promising therapeutic platform for cancer. Abstract : In this work, two strategies are examined to intensify the absorption/fluorescence and fluorescence/photoacoustic imaging performance of benzobisthiadiazole moieties. Nanoparticles that feature the optimized moiety perform real‐time and high‐contrast noninvasive near‐infrared fluorescence/photoacoustic imaging of tumors (980 nm laser irradiation), and also effectively ablate tumor cells by photothermal therapy, and thus implementing the dual‐modality imaging method.